Community Empowerment Through Socialization of Eco-Friendly Paving Block Production from Plastic Waste in 26 Ilir Sub-district, Palembang City - Imam Akbar; Dewi Rawani; Pramadhony (CV. Doki Course and Training, 2025)
Plastic waste remains a serious challenge in urban areas, including in 26 Ilir Sub-district, Palembang City, with significant impacts on both the environment and public health. Innovative efforts are therefore required to reduce waste volume while simultaneously providing economic benefits for residents. This community service program aimed to provide education and skills to the local community through socialization and hands-on practice in producing paving blocks from plastic waste using simple steel molds. The program was implemented in several stages: preparation, socialization, demonstration and practice, mentoring, and evaluation with feedback. The results showed high community participation with cross-generational involvement. Public understanding of the impacts of plastic waste increased significantly, from 52% before the program to 87% after. Participants were also able to independently practice paving block production, including the fabrication of simple steel molds. The paving blocks produced were dense and suitable for use in neighborhood roads. Community feedback indicated that 72% of participants were interested in continuing the program and forming small business groups focused on plastic recycling. Thus, the program successfully enhanced awareness, knowledge, and practical skills in plastic waste management. Beyond improving environmental cleanliness, it also opened new entrepreneurial opportunities that support the concept of a circular economy at the community level.